2007
DOI: 10.1111/j.1745-7262.2007.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of vitamin E on ethane dimethane sulfonate-induced testicular toxicity in rats

Abstract: Vit E cotreatment showed partial protective effects on the testicular weight and testicular histology in rats that received EDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Vitamin E @ 100 mg/kg b. wt was found to be ineffective to protect testicular tissues against radiation-induced damage. [19] Partial protective role of vitamin E was recorded earlier during ethane dimethane sulfonate-induced[20] testicular toxicity in rats. Vitamin E has been proven to protect testicular tissues against experimental cryptorchidism in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin E @ 100 mg/kg b. wt was found to be ineffective to protect testicular tissues against radiation-induced damage. [19] Partial protective role of vitamin E was recorded earlier during ethane dimethane sulfonate-induced[20] testicular toxicity in rats. Vitamin E has been proven to protect testicular tissues against experimental cryptorchidism in rats.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the reduction in volume and weight of testis, diameter of seminiferous tubules, thickness of germinal epithelium, number of sperm, spermatogenesis and the induction of apoptosis in the germ cells are some of the changes that have been reported as the consequences of p-NP exposure [11][12][13][14][15][16]. On the other hand, antioxidants, such as vitamin E, can inhibit reactive oxygen species (ROS) [9,17,18], and thus terminate lipid peroxidation and stabilize the molecular composition of cellular membranes [19]; therefore, it prevents the harmful effects of ROS. In addition, investigations have also shown that the vitamin E prevents toxic damages to testis and sperm after exposure to other chemicals and to γ-radiation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, antioxidants, such as vitamin E, can inhibit reactive oxygen species (ROS) [9,17,18], and thus terminate lipid peroxidation and stabilize the molecular composition of cellular membranes [19]; therefore, it prevents the harmful effects of ROS. In addition, investigations have also shown that the vitamin E prevents toxic damages to testis and sperm after exposure to other chemicals and to γ-radiation [19][20][21]. As vitamin E is a dietary factor for animal nutrition, which is important for normal reproduction [22], and also its requirement for testicular function is well established [23], therefore, this study was organized to investigate the preventing role of vitamin E as a strong antioxidant in ameliorating the undesired effects of p-NP on the structure of testis in rats treated with p-NP from prenatal to maturation for a period of 90 days.…”
Section: Introductionmentioning
confidence: 99%
“…DMSO was used as a vehicle in several in vivo studies. According to Sahinturk, Guclu, and Baycu () “The vehicle (DMSO)‐treated control rats showed the typical morphological organisation of the adult rat testis.” Similarly, Yucra et al. () found no difference between rats treated with DMSO or distilled water.…”
Section: Discussionmentioning
confidence: 99%